2017
DOI: 10.2147/ccid.s124886
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fatigue and its correlation with quality of life index, anxiety symptoms, depression and activity of disease in patients with psoriatic arthritis

Abstract: BackgroundPsoriatic arthritis is associated with psychosocial morbidity and decrease in quality of life. Psychiatric comorbidity also plays an important role in the impairment of quality of life and onset of fatigue.ObjectivesThis study aimed to assess the prevalence of fatigue in psoriatic arthritis patients and to correlate it to quality of life indexes, functional capacity, anxiety, depression and disease activity.Patients and methodsThis cross-sectional study was performed on outpatients with psoriatic art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 58 publications
(50 reference statements)
1
24
0
Order By: Relevance
“…We found a high correlation between fatigue and depressive symptoms, which was similar to a previous study (Carneiro et al, ). Because fatigue is a symptom with a multi‐dimensional impact, it is difficult to describe it explicitly.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found a high correlation between fatigue and depressive symptoms, which was similar to a previous study (Carneiro et al, ). Because fatigue is a symptom with a multi‐dimensional impact, it is difficult to describe it explicitly.…”
Section: Discussionsupporting
confidence: 92%
“…It has a complex relationship with pain and physical activity in women with OA, and is the strongest predictor of physical activity levels in older people with knee and hip OA (Murphy et al, ; Snijders et al, ). In addition, fatigue is related to depression and poorer quality of life in people with psoriatic arthritis (Carneiro et al, ), and is associated with both clinical and psychological conditions in people with knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…1). Ultimately, 66 of the 84 studies were excluded from inclusion in the systematic literature review (Table 1) [12,, and 18 articles were included [9,14,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98], one of which had been identified from the hand search (see Tables 2 and 3 for more detail).…”
Section: Resultsmentioning
confidence: 99%
“…The impact of the disease on HRQoL is comparable to other diseases. In arthritis, a number of studies have demonstrated significantly lower quality of life compared to the general population both in patients with rheumatoid arthritis [33][34][35][36][37] and in those with psoriatic arthritis [38][39][40][41] . This underlines the need for new treatment options.…”
Section: Discussionmentioning
confidence: 99%